Effectiveness of Erythropoietin in Hypertensive Hemodialysis Patients - Ibrahim, Susannia; Diantini, Ajeng; Prihartanto, Budhi; Supriyadi, Rudi (Pharmacology and Clinical Pharmacy Research)
Chronic renal failure (CRF) is one the most prevalent health problems among the elderly. Onthe fifth stage of CRF, the patient becomes eligible to hemodialysis. CRF-induced anemiais commonly treated with Erythropoietin (Epo). Information regarding the effectiveness ofEpo in hypertensive hemodialysis patients was limited. Therefore, this study was conductedto evaluate the effectiveness of Epo in hypertensive hemodialysis patients. This study usedan observational case-control analytic method. Data were retrieved from the medical recordsof hemodialysis patients during March-May 2014. A total of 54 participants were included.The increase of haemoglobin (Hb) in controlled hypertension was 0.6257 g/dl, while the inuncontrolled hypertension group, there was a decrease in Hb (-0.1590 g/dl). The use of Epowas more effective in hemodialysis patients with controlled hypertension.Keywords: chronic kidney disease, erythropoietin, hypertension